2018
DOI: 10.1097/jfn.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Control and Instability: Insight Into Head Injury From Intimate Partner Violence

Abstract: Aim: The aim of this study was to understand the social context of the lives of women who experienced a head injury from intimate partner violence. Background: Sixty percent to 92% of survivors of intimate partner violence receive head trauma during the abuse. Little research exists regarding the episodes of abuse when women receive a head injury, or the reasons women might not seek medical care for the head injury or the abuse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Ivany & Schminkey, 2016; St. Ivany et al, 2018a, 2018b; Valera et al, 2018). Physical symptoms include headaches, fatigue, sleep disturbances, vertigo, and pain, while cognitive symptoms affect attention, concentration, and executive functioning, suggesting interventions should serve to strengthen the capacity of the survivor to process and interpret information (Corrigan et al, 2003; Jackson et al, 2002; Murray et al, 2016; Valera & Berenbaum, 2003; Valera et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ivany & Schminkey, 2016; St. Ivany et al, 2018a, 2018b; Valera et al, 2018). Physical symptoms include headaches, fatigue, sleep disturbances, vertigo, and pain, while cognitive symptoms affect attention, concentration, and executive functioning, suggesting interventions should serve to strengthen the capacity of the survivor to process and interpret information (Corrigan et al, 2003; Jackson et al, 2002; Murray et al, 2016; Valera & Berenbaum, 2003; Valera et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The onus of screening, assessment, and triage for IPV largely falls on frontline professionals in health-care and community contexts. As early screening and intervention can lead to improved outcomes, routine screening for TBI when IPV is disclosed or suspected was encouraged by a number of authors (Ackerman & Banks, 2009; Amoroso & Iverson, 2017; Baumann et al, 2018; Campbell et al, 2018; Corrigan et al, 2003; Davis, 2014; Farley et al, 2018; Iverson et al, 2017; Iverson & Pagoda, 2015; Jackson et al, 2002; Monohan & O’Leary, 1999; Murray et al, 2016; Smith & Holmes, 2018; Stern, 2004; St. Ivany, Kools, Sharps,& Bullock, 2018b; Zieman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that frequent control via psychological abuse overlapped with an increased risk of danger in abused women and a head injury became a way to exhibit an extreme form of control including removing the women's ability to seek external help (St Ivany et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…M. Valera, 2018; E. M. Valera et al, 2019), despite increasing evidence of the high risk for BI in this vulnerable population (Baxter & Hellewell, 2019; Goldin et al, 2016; Haag et al, 2019; Kwako et al, 2011; St Ivany, Kools et al, 2018).…”
Section: Introductionmentioning
confidence: 99%